MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI OPERASI HITUNG CAMPURAN SISWA KELAS IV SD DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) - Priatna, Asep; Safitri, Fahma (STKIP Subang, 2017)
Application of Experimental Methods to Increase Understanding of the Concept of Grade IV Primary School Students in Science Lesson. The purpose of this study is to describe data on: (1) student activity in science learning by applying experimental method; (2) improvement of understanding of science concept by applying experiment method. The method used in this research is a classroom action research with Kemmis n Mc design. Taggart. This research was conducted in the odd semester of academic year 2017/2018 at SD Negeri Wirukencana in grade 4 students. Data collection techniques used are observation, test and documentation. Based on the processing and data analysis, the results of this study are: (1) Student activity at the time of learning using experimental method that is in the first stage students pay attention to the initial experiments conducted by the teacher as evidenced by answering questions asked by teachers around the experiment. Then at the observation stage all the students recorded things that happened while observing the experiments performed by the teacher. The third stage of the students make a hypothesis according to the conceptual observation based on observation. Furthermore, in the verification stage students conduct experiments that refer to the LKS in a group way, the students divide each task on each member of the group such as the task as chairman of the group, secretary, moderator and other tasks in the experiment. After the students complete the experiment each group discuss or present the results of his group's observations in front of the class. The fifth stage is the application of concepts, the students are able to give examples of the alteration of changes in the form of things in everyday life; and (2) The application of experimental methods in general can increase the understanding of the concept of fourth grade students.